Effect of Biofertilizer Addition on Nitrous Oxide Emission - Endah Retnaningrum; Irfan D. Prijambada; Sukarti Moeljopawiro; Budi S. Daryono (Journal of Basic & Applied Sciences, 2021)
Application of nitrogen fixing biofertilizer, such as Azotobacter, has a potential for reducing nitrous oxide(N2O) emission. The aim of this study was to examine the effect of nitrogen fixing biofertilizer addition to common practices of urea and fresh cattle manure usages for maize (Zea mays L.) growing on N2O emission. The field experiment was conducted at GunungKidul, Yogyakarta, Indonesia. The treatments were addition of fresh cattle manure (M), fresh cattle manure added with nitrogen fixing biofertilizer (MB), urea (U), urea added with nitrogen fixing biofertilizer (UB), and control (no N fertilizer added). Nitrogen contents of the added urea and fresh cattle manure were adjusted to be equal. Urea and fresh cattle manure were given three times throughout the experiment period, i.e. 12, 30, and 48 days after planting (DAP). Urea was given at a rate of 44, 29, and 15 kg.ha-1, respectively while fresh cattle manure was given at a rate of 6000, 4000, and 2000 kg.ha-1, respectively. The emitted N2O was collected using a closed-chamber method at 24, 42, 60, and 72 DAP and were determined using Gas Chromatograph. Soil properties including available N (NH4+-N and NO3–-N) and organic C contents were also analyzed. On the harvesting time, the harvest index and the grain yield were determined. Biofertilizer addition influence decomposition process of cattle manure and urea that led to mineralization and nitrification of residual organic matterand hence to cause soil NH4+N in the order concentration of M treatment > MB > U > UB>C, and soil NO3–-N of MB treatment > M > U > UB>C. Reduction of NO3–N was resulted in the highest N2O emission of M >U>MB>UB>C(P < 0.01). The grain yield, and harvest index of maize wereresulted in the order value of MB> UB > U > M>C treatments.Available mineral N and soil organic C contents strongly affected N2O emission (P < 0.01).The results suggested that biofertilizer addition to common agricultural practices reduce N2O emission and simultaneusly increased grain yield, and harvest index of maize.